Kompetensi Karyawan Operasional Bongkar Muat dalam Pencapaian Berthing Time - Guntur Angkoso; Aswanti Setyawati (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2019)
PT Mustika Alam Lestari is a container loading and unloading service at Tanjung Priok Port, Jakarta. The service prioritizes on the customers’ needs, by having competent operational employees and available loading and unloading equipment,  so that the berthing time is well achieved. This study aims to analyze the effect of operational employee competency and loading and unloading equipment on berthing time. The research method used was descriptive verification with data analysis using multiple linear regressions. Primary data were collected through the distribution of questionnaires with 61 people as the samples from operational division employees at PT Mustika Alam Lestari, Jakarta. The result of this research is the success in berthing time is the integration of operational employees’ competence and loading and unloading equipment. The results of hypothesis testing indicate that operational employees’ competence and loading equipment show a positive and significant effect on berthing time.